Environmental DNA metabarcoding reveals spatial and seasonal patterns in the fish community in the Venice Lagoon - Cananzi, Gabriele; Gregori, Irene; Martino, Francesco; Li, Tianshi; Boscari, Elisa; Camatti, Elisa; Congiu, Leonardo; Marino, Ilaria Anna Maria; Pansera, Marco; Schroeder, Anna; Zane, Lorenzo (Frontiers in Marine Science, 2022)
Environmental DNA (eDNA) is an emerging tool for assessing biodiversity and understanding spatial and temporal community patterns and processes, directly from DNA sequencing of environmental samples such as air, water, and sediments. We applied eDNA methods to monitor bony fish communities, detecting as well locally allochthonous species, and to reveal seasonal patterns at two sites in the Venice Lagoon. We analyzed 17 water samples collected over 12 months at two ecologically distinct sites by using available primers for teleosts and High Throughput Illumina sequencing. We identified 1,289 amplicon sequence variants (ASVs) assigned to 62 fish taxa. Most of the species known to inhabit or to enter the Venice Lagoon were detected, with eDNA data reflecting differences in fish communities between the internal (freshwater associated) and the external (sea associated) part of the lagoon. Moreover, seasonal trends of migration have been portrayed, highlighting the most involved species and disclosing possible clashes between migration events and the temporary interruption of sea-lagoon connectivity due to MOSE (MOdulo Sperimentale Elettromeccanico). Of interest, the first-time detection of Oceanic puffer (Lagocephalus lagocephalus) DNA in the Venice Lagoon provides evidence of the further northward expansion of this species in the high Adriatic Sea. eDNA successfully profiled fish communities by season and habitat in the Venice Lagoon. Our results support routine application of eDNA to monitor potential ecological consequences of MOSE closures in this World Heritage site.